Labour markets and human resource planning in Asia : perspectives and evidence - Muqtada, M.; Hildeman, A. (New Delhi, India : Asian Regional Team for Employment Promotion, 1993)
Contributed articles.
Includes bibliographical references and index.
Keywords: Manpower policy -- Asia; Labor market -- Asia